Active Seismic Exploration of Planetary Subsurfaces via Compressive Sensing - Jingchuan Wang; Nicholas C. Schmerr; Vedran Lekić; Jacob Giles; Linden Wike; Austin Hoyle; Ernest Robert Bell; Naoma McCall; Jacob A. Richardson; Patrick Whelley; John D. West; Shannon Rees; et al. (Earth and Space Science)
Abstract Geophysical measurements, such as seismic experiments, are a key target for scientific activities on planetary surfaces. Dense spatial sampling of such measurements is often desirable, and acquisition is traditionally performed at regular intervals. However, achieving regular and dense spatial sampling is made difficult by obstacles and operational constraints of a planetary surface mission. Here, we present an application of compressive sensing (CS) in the design of seismic surveys on planetary surfaces for imaging the shallow subsurface. This approach is based on more flexible, randomized subsampling and requires fewer sources or receivers compared to traditional methods. We illustrate the potential of CS on synthetic data and measurements made along an active seismic transect across a lunar analog site. We then explore the use of CS‐assisted seismic acquisition at a terrestrial analog site in the San Francisco Volcanic Field. We show how irregularly acquired data can be interpolated to reconstruct data at finer spatial sampling and yield seismic images comparable to those from regularly acquired high‐density data. Finally, we apply our approach to reanalyze the legacy data collected by the Active Seismic Experiments during the Apollo 14 and 16 missions. The results show that the CS method can recover missing data and increase the amount of data available for refraction analysis. Our study highlights the potential of CS in future planetary surface exploration missions for (a) an order‐of‐magnitude improvement in survey efficiency and (b) improved imaging quality to gain a deeper understanding of the geologic processes of planetary bodies.